Amyloidogenic immunoglobulin light chains disturb contractile function and calcium transients in a human cardiac spheroid model of light chain (AL) amyloidosis - Mélanie Bézard; Jean-Sébastien Vartanian-Grimaldi; Julien Henri; Denisa Calin; Amira Zaroui; Mounira Kharoubi; Thibaud Damy; Onnik Agbulut; Ekaterini Kordeli (Scientific Reports)
Abstract Light chain (AL) amyloidosis is a serious systemic disease caused by the deposition of free misfolded immunoglobulin light chains (LCs) in the form of amyloid fibrils within tissues. Cardiac involvement determines prognosis and mortality. An important cytotoxic impact of amyloidogenic prefibrillar LC oligomers on cardiomyocytes is by now established in isolated rodent cardiomyocytes, simple animal models, or cardiomyocyte-like cell lines. However, the response of human cardiomyocytes to this pathogenic condition is currently unknown. In this work, we have set up a human cellular disease model of AL cardiac amyloidosis (AL-CA) in the form of cardiac spheroids, to study the cytotoxic effects of amyloidogenic LCs with regard to contractile function and calcium handling. To mimic the disease in a reconstituted system, soluble amyloidogenic LCs purified from urine of AL-CA patients were added to a mixture of induced pluripotent stem cell-issued human cardiomyocytes (hiPSC-CM) and human primary cardiac fibroblasts, which resulted in formation of spheroids within 7 days. This procedure ensured a uniform pericellular LC distribution within spheroids. LC-treated hiPSC-CM cultures and LC-containing spheroids presented structural and functional defects including: (1) decreased levels and subcellular disorganization of sarcomeric protein alpha-actinin; (2) abnormal accumulation of calcium handling SERCA2a protein; (3) impaired contractility of spheroids and altered calcium transients. Three independent patient-derived LCs had similar effects, albeit to varying degrees, highlighting the patient-specific properties of this type of amyloids. Taken together, these results indicate that the present cardiac spheroid disease model could be appropriate to the study of cardiac cytotoxicity caused by different amyloidogenic LCs in AL-CA patients, contributing to a better understanding and therapeutic handling of the disease.